Biological study of pomegranate fruits and their active components for some types of isolated bacteria from diarrhea cases in the city of Mosul - Khader Suleiman (College of Education for Pure Sciences, 1999)
Abstract: The study involved isolation and identification of the bacteria types which cause effection to the stomach from peoples having dieria-200 saples of diaria patients male and female of different ages were used in this study during aperiod of sepetemlar 2006-march 2007. The isolated microorganisms were as follows. Entero pathogenic, E.coli O126 in percent of 38.88% Which y the most popular percent then Sal. Typyimurium with apercent of 27%in so 1% typh and Sh.flexneri, Apercent of 16-11%. The result of the above study revailed that aquous extract of punica granatum has medium activity agaius all types of bacteria studied compaired with antibiotic cephalexin and showed weak activity comparied to the Gentamycin, Trimethoprim antibiotics. The alcohole extract showed higher activity against all types of bacteria compaired with antibiotics (Gentamycin, cephalexin). Moderate activity was shown compaired with Trimethoprim. The study also revailed that the extract of punica granatum showed higher tow and all types of bacteria comparied with the commercial antibiotic mentioned above. The diometer of inhibition one of Sh.flexneri was found 23mm While for S. Typhi y 22mm. The determination of minimum concentration activity (MIC) of the aquous extracts was found 1mg/ml. For Sh.flexneri, S. Typhi and S.Typyimurium, while for E.coli was 0.5 mg/ml. The (MIC) of alcoholic extracts for all studied bacteria was found 0.25 mg/ml. The punica granatum extract was found equd in activity for Sh.flexneri, S. Typhi and S.Typyimurium whoch y 0.125mg/ml. While in E.coli the minimum activity (MIC) was found 0.25 mg/ml. The minimum Killer concentration (MBC) was also determined in this study for the studied organisms. The aquous extract for Sh.flexneri, S.Typyimurium was found 2 mg/ml. For E.coli it was found 1 mg/ml. Alcoholic of all types of organisms as (MBC) was found 0.5 mg/ml. The punica granatum extract was found 0.5 mg/ml. for all types of bacteria studied. The detection of the inhibitory effect for the separated tannin in the growth of the (EPEC O126 in vivo using the ILLeaL rabbit Loop test Showed that the Tannin has an inhibitory effect in the (EPEC) O126 though the measurement of the dilatation indicator Wich was showed to be (0.37) and in comparison with the other dilatation in dicator measurement.